PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM ) PADA TOKO URBAN TRAFFIC BERBASIS WEB - Aryo Nur Utomo; Reza Christiando Purba (JURNAL REKAYASA INFORMASI, 2022)
In a business, the customer is a very important factor. For that, it is necessary to build a good relationship between the company and the customer. One of the obstacles faced by cake shops today is how to obtain and provide information from and to customers quickly. To meet the need for information that is fast, accurate, and has a wide reach, both for customers and the store, a web-based customer information system is needed that can be accessed online by customers. This web-based customer information system is integrated with a database that will store the required data. The results of the implementation of the implementation of the Customer Relationship Management method make it easy for customers to find out what products are sold and make product orders quickly. The system that will be designed focuses on helping customers to get information about products and companies, and helping customers in the online purchasing process. Information System Application of CRM Concepts on Web-Based Urban Traffic built using PHP and MySQL Database Key words : customer, PHP, MySQL Database, Information Sistem, CRM Concept, Urban Traffic Store